2006
DOI: 10.1021/nl060060o
|View full text |Cite
|
Sign up to set email alerts
|

Myotube Assembly on Nanofibrous and Micropatterned Polymers

Abstract: Skeletal muscle consists of parallel bundles of myotubes formed by the fusion of myoblasts. We fabricated nanofibrous and micropatterned polymers as cell culture substrates to guide the morphogenesis of muscular tissue. The nanoscale and microscale topographic features regulate cell and cytoskeleton alignment, myotube assembly, myotube striation, and myoblast proliferation. This bottom-up approach from nanoscale to tissue level demonstrates the potential of nanofibrous polymers for engineering the assembly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
265
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 300 publications
(281 citation statements)
references
References 25 publications
9
265
2
Order By: Relevance
“…After washing away the unpolymerized photoresist, PDMS was prepared according to the manufacturer's protocol (Sylgard 184; Dow Corning, Midland, MI), spin-coated onto the patterned silicon wafers to desired thickness (Ϸ250 m), degassed under vacuum, and cured at 70°C for 1 h. The resulting micropatterned membranes were removed from the template, cut to appropriate dimensions (for assembly into custom-built stretch chambers), and thoroughly washed and sonicated before use. The surface topography of micropatterned PDMS membranes was examined by scanning electron microscopy (27). Mechanical testing showed that PDMS membranes were elastic under cyclic uniaxial strain (Ͻ30% strain, 1 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…After washing away the unpolymerized photoresist, PDMS was prepared according to the manufacturer's protocol (Sylgard 184; Dow Corning, Midland, MI), spin-coated onto the patterned silicon wafers to desired thickness (Ϸ250 m), degassed under vacuum, and cured at 70°C for 1 h. The resulting micropatterned membranes were removed from the template, cut to appropriate dimensions (for assembly into custom-built stretch chambers), and thoroughly washed and sonicated before use. The surface topography of micropatterned PDMS membranes was examined by scanning electron microscopy (27). Mechanical testing showed that PDMS membranes were elastic under cyclic uniaxial strain (Ͻ30% strain, 1 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were fi xed in 4% paraformaldehyde and immunofl uorescently stained, as described previously [ 21 ], for the antibodies sGCα 3 (Sigma, St. Louis, MO), sGCβ 3 (Sigma), eNOS, or CD144 (BD Biosciences, San Diego, CA). Total nuclei were stained by Hoechst 33342 (Invitrogen, Carlsbad, CA) dye before imaging on a fl uorescent microscope (Nikon, Burlingame, CA), and images were captured with a SPOT RT color camera (Diagnostic Instruments, Sterling Heights, MI).…”
Section: Immunofl Uorescence Stainingmentioning
confidence: 99%
“…11 Consequently, changes in muscle tissue architecture in physiological (e.g., fiber rotation during shortening of pennate muscle 12 ) or pathological (e.g., muscle disarray and fibrosis in dystrophic muscle 13 ) conditions can significantly affect generation of muscle contractile force. To recreate native muscle architecture in vitro, researchers have previously applied different topographical, 14 chemical, [15][16][17] or physical 18 cues to align cells in 2D culture, or utilized cylindrically shaped cell-laden hydrogels or self-assembled organoids formed under static uniaxial tension to align muscle cells in 3D culture. 4,8,9,19 However, no current tissue engineering methodologies allow for precise and reproducible control of local 3D myofiber alignment that would enable systematic studies of structure-function relationship encountered in healthy, diseased, or developing skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%